Drosophila CtBP regulates proliferation and differentiation of eye precursors and complexes with Eyeless, Dachshund, Dan, and Danr during eye and antennal development. - Hoang, C.Q.; Burnett, M.E.; Curtiss, J. (Developmental Dynamics, 2010)
Specification factors regulate cell fate in part by interacting with transcriptional co-regulators like CtBP to regulate gene expression. Here, we demonstrate that CtBP forms a complex or complexes with the Drosophila melanogaster Pax6 homolog Eyeless (Ey), and with Distal antenna (Dan), Distal antenna related (Danr), and Dachshund to promote eye and antennal specification. Phenotypic analysis together with molecular data indicate that CtBP interacts with Ey to prevent overproliferation of eye precursors. In contrast, CtBP,dan,danr triple mutant adult eyes have significantly fewer ommatidia than CtBP single or dan,danr double mutants, suggesting that the CtBP/Dan/Danr complex functions to recruit ommatidia from the eye precursor pool. Furthermore, CtBP single and to a greater extent CtBP,dan,danr triple mutants affect the establishment and maintenance of the R8 precursor, which is the founding ommatidial cell. Thus, CtBP interacts with different eye specification factors to regulate gene expression appropriate for proliferative vs. differentiative stages of eye development.